Enhancing sustainable innovation through collaborative knowledge absorption: Insights from the development of a hybrid marine engine - Jingjing Ge; Sandra Hasanefendic; Bart Bossink (PLoS ONE, 2026)
Rapid technological advancements, characterized by uncertainties, together with the growing imperative for environmental sustainability, are continuously reshaping markets and business strategies. These developments necessitate integrating sustainable innovation with effective knowledge absorption to promote technological progress. While prior research has primarily examined drivers of sustainability at the macro level, comparatively limited attention has been given to the processual and micro-level dynamics through which sustainable innovation unfolds. As a result, the underlying mechanisms, individual actions, and collaborative knowledge processes that shape sustainable innovation remain insufficiently theorized and empirically explored. To address this gap, this study draws on effectuation theory and absorptive capacity to conceptualize sustainable innovation as an iterative, stakeholder-driven process in which knowledge is acquired, assimilated, transformed, and exploited. Empirically, the study adopts an in-depth case analysis of the development of a hybrid marine engine – i.e., a propulsion system for vessels that combines a conventional combustion engine with electric propulsion from batteries – to refine this framework. The results identify five distinct phases of the sustainable innovation process, each influenced by specific dimensions of individuals’ collaborative knowledge absorption. This study contributes to the sustainability and innovation literature by integrating insights from effectuation, knowledge absorption, and entrepreneurial behavior into a structured framework. In doing so, it provides both theoretical advancement and practical guidance for policymakers and business practitioners seeking to foster sustainable innovation in technology-driven contexts.